Same Sex Marriages - Heaphy, B. author. aut Link
X, 205 p.
Keywords: Based on extensive couple and individual interviews with young same sex couples who have legally formalized their relationships, this book argues that same sex marriages as they are lived need to be understood in terms of interlinked developments in lesbian and gay life, heterosexual relationships and in personal life.